2015
DOI: 10.1007/s00408-015-9703-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of a 12-Week Exercise Training Program on Clinical Outcomes in Idiopathic Pulmonary Fibrosis

Abstract: At 11-month follow-up, the 12-week ET program showed clinical outcomes were preserved at baseline levels with some maintenance of improvements in leg strength and QOL in the ET group. The control group showed a trend of deterioration in the outcomes. At 30 months, the 12-week ET program did not show benefits in prognosis although the study was underpowered to detect such differences. We suggest including ET as a long-term continued treatment and as a core component of pulmonary rehabilitation programs for IPF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(144 citation statements)
references
References 42 publications
5
128
1
10
Order By: Relevance
“…We also found that non-survivor subjects were characterized by a higher prevalence of pulmonary hypertension, a lower level of exercise capacity, more severe desaturation, and higher dyspnea levels with evident breathing inefficiency compared with survivors (Table 4). Consistent with our previous report, 38 the current study did not show benefits in survival following exercise training intervention at 40-month follow-up (see Fig. 1), although this study was underpowered to detect such differences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We also found that non-survivor subjects were characterized by a higher prevalence of pulmonary hypertension, a lower level of exercise capacity, more severe desaturation, and higher dyspnea levels with evident breathing inefficiency compared with survivors (Table 4). Consistent with our previous report, 38 the current study did not show benefits in survival following exercise training intervention at 40-month follow-up (see Fig. 1), although this study was underpowered to detect such differences.…”
Section: Discussionsupporting
confidence: 92%
“…42 It could be argued that an additional limitation of the study is related to the subjects' group assignments for exercise training or usual care, which could have some impact on the results and potential bias. This hypothesis was rebutted in our previous 38 and current reports (see Fig. 1), showing no significant differences in survival between exercise training and the control group; however, the studies were underpowered to detect survival differences.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…[17][18][19] These studies show the importance of the pulmonary rehabilitation program to patients with ILD. The pulmonary rehabilitation program, which includes physical exercise, has positive results in endurance capacity 20,21 and improves the symptoms and life quality of these patients. 22 Exercise physiology has used laboratory animals to simulate conditions of physical stress observed in humans and its purpose is to better monitor the systemic, cellular, and molecular changes resulted from physical activity.…”
Section: Introductionmentioning
confidence: 99%